Sistem Pendukung Keputusan Pemilihan Santri Terbaik Menggunakan Metode Vikor Berbasis Web Pada Pesantren Darul Ihsan - Dani Irwansyah; Charles Bronson Hrp (Lembaga Pengembangan Kinerja Dosen, 2025)
Because Islamic boarding schools use a manual assessment system that tends to be subjective, it is often difficult to select the best students. The VIKOR (VIseKriterijumska Optimizacija I Kompromisno Resenje) method was used in this study to design and implement a web-based Decision Support System (DSS). The purpose of this study was to find the best students at Darul Ihsan Islamic Boarding School quickly, fairly, and effectively. Examination scores, attendance, memorization of the Qur'an, participation in extracurricular activities, and non-academic achievements are all criteria used to assess a person. Needs analysis, system design, implementation, and system testing using Blackbox are all steps in Waterfall software development. PHP and MySQL databases were used to create this system. The results of the study show that the DSS built has the ability to produce fair and unbiased student rankings. The VIKOR method has been proven effective in producing fair compromise solutions that balance academic and non-academic standards. It is hoped that this system will help Islamic boarding schools make better and more honest decisions.